2005
DOI: 10.1101/gr.4319006
|View full text |Cite
|
Sign up to set email alerts
|

Variation in crossing-over rates across chromosome 4 of Arabidopsis thaliana reveals the presence of meiotic recombination “hot spots”

Abstract: Crossover (CO) is a key process for the accurate segregation of homologous chromosomes during the first meiotic division. In most eukaryotes, meiotic recombination is not homogeneous along the chromosomes, suggesting a tight control of the location of recombination events. We genotyped 71 single nucleotide polymorphisms (SNPs) covering the entire chromosome 4 of Arabidopsis thaliana on 702 F2 plants, representing 1404 meioses and allowing the detection of 1171 COs, to study CO localization in a higher plant. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

20
143
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(166 citation statements)
references
References 69 publications
(72 reference statements)
20
143
0
3
Order By: Relevance
“…In Arabidopsis, putative hot spots have been reported in short regions (a few kilobases) on Chr4 (Drouaud et al 2006). Here, one CO on Chr4 was in one of these regions (Supplemental Fig.…”
Section: Single-base Resolution Analysis Of Cos and Ncos/gcsmentioning
confidence: 95%
“…In Arabidopsis, putative hot spots have been reported in short regions (a few kilobases) on Chr4 (Drouaud et al 2006). Here, one CO on Chr4 was in one of these regions (Supplemental Fig.…”
Section: Single-base Resolution Analysis Of Cos and Ncos/gcsmentioning
confidence: 95%
“…Further, a recombination hotspot has been identified in a highly gene-rich region at the maize bz locus and characterized at a fine scale (Fu et al 2001). In contrast, in Arabidopsis (Drouaud et al 2006) fine-scale analysis failed to establish a correlation between recombination and gene density.…”
mentioning
confidence: 99%
“…Their distribution can be analyzed by comparing physical and genetic maps or by studying linkage disequilibrium patterns. Studies performed in human, mouse, Arabidopsis, and rice (Wu et al 2003;Drouaud et al 2006;Arnheim et al 2007) provided insight into some of the major features of recombination distribution with the identification of hot and cold regions of recombination along the chromosomes as well as a general suppression of COs in centromeric and pericentromeric regions (for a review see Jones 1987). In some plants with large genomes such as maize [2.5 Gigabase (Gb)], barley (5 Gb), and wheat (17 Gb), recombination was shown to follow particular patterns with a gradual increase from the centromeres to the telomeres (Lukaszewski and Curtis 1993;Kunzel et al 2000;Tenaillon et al 2001;Anderson et al 2003).…”
mentioning
confidence: 99%
“…GC content represents perhaps the most prominent property for which strong correlations with recombination were reported for the genomes of many organisms including mammals, Drosophila melanogaster, Caenorhabditis elegans, and Saccharomyces cerevisiae (Gerton et al 2000;Marais et al 2001;Birdsell 2002;Kong et al 2002;Meunier and Duret 2004). On the other hand it was recently demonstrated that in Arabidopsis thaliana rate of crossover and GC content are not correlated (Drouaud et al 2006). However, despite these numerous results, it is not clear as yet (1) whether recombination drives GC content or the converse and (2) what are the length scales for the correlations between GC and recombination.…”
mentioning
confidence: 99%